From Pluralism to Unification: The Transformation of Marriage Law in Indonesia Before and After the 1974 Marriage Law - Uswatun Hasanah; Ridho Abdillah; Tufatul Kholisoh; Humaeroh Humaeroh (Journal of Human Interaction and Social Studies, 2026)
This study examines the historical transformation of marriage law in Indonesia from a plural legal structure inherited from the colonial period to a unified national legal framework established through Law Number 1 of 1974 concerning Marriage. Employing a non empirical qualitative approach based on library research, the study analyzes primary legal sources including Law Number 1 of 1974, Government Regulation Number 9 of 1975, Government Regulation Number 10 of 1983, the Compilation of Islamic Law of 1991, Law Number 16 of 2019, and Constitutional Court Decision Number 22/PUU XV/2017. Secondary sources consist of scholarly publications addressing legal pluralism, family law reform, gender equality, and child protection. The findings demonstrate that the 1974 Marriage Law constituted a fundamental shift from fragmented legal regimes based on religion and social classification toward a national system emphasizing legal certainty, marriage registration, monogamy, and equal legal standards. Subsequent reforms strengthened administrative regulation and expanded protection of women and children. Despite these developments, challenges concerning interfaith marriage, customary communities, legal pluralism, and human rights continue to influence the contemporary development of Indonesian marriage law.